1987
DOI: 10.1139/v87-242
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure of rolliniastatin 1 from the South American tree Rolliniamucosa

Abstract: in primitive medical practices of Indonesia and the West Indies as a treatment for tumors, has been investigated employing the seeds from a South American variety and the murine P388 lymphocytic leukemia (PS) for bioassay. The principal antineoplastic constituent (PS, 28% life extension, at 0.25 mg/kg and EDso4.5 X kg/mL) was found to be a new bis-tetrahydrofuran designated rolliniastatin 1. Structural elucidation of rolliniastatin 1 was accomplished by a combination of high resolution nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 1 publication
4
62
0
5
Order By: Relevance
“…The fruit is regarded as a refrigerant, analeptic, and anti-scorbutic, while the powdered seeds are said to be a remedy for enterocolitis (Morton, 1987). Chemical investigations of this species reported the presence of acetogenins with antineoplastic and cytotoxic activities in seeds and leaves (Pettit et al, 1987;Shi et al, 1997). In addition, we reported that the furafuranic lignans, (+)-epieudesmine and (+)-epimagnolin, and the linear C 31 -ketone palmitone (16-hentriacontanone), were the principal constituents of the hexane extract of leaves of R. mucosa (Estrada-Reyes et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…The fruit is regarded as a refrigerant, analeptic, and anti-scorbutic, while the powdered seeds are said to be a remedy for enterocolitis (Morton, 1987). Chemical investigations of this species reported the presence of acetogenins with antineoplastic and cytotoxic activities in seeds and leaves (Pettit et al, 1987;Shi et al, 1997). In addition, we reported that the furafuranic lignans, (+)-epieudesmine and (+)-epimagnolin, and the linear C 31 -ketone palmitone (16-hentriacontanone), were the principal constituents of the hexane extract of leaves of R. mucosa (Estrada-Reyes et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Grubbs and coworkers utilized 9 in this transformation, as 9 is highly Z-selective and promotes the formation of anti-diols [173]. Many stereodefined anti-diols containing various functionalities could be prepared using this method (Table 22) Tetrahydrofuran (THF) diols are found in a wide variety of natural products [174][175][176][177]. A convenient method for the formation of THF diols is through the oxidative cyclization of 1,5-dienes to form 2,5-disubstituted THF diols.…”
Section: Stereoselective Olefin Metathesis In Synthetic Applicationsmentioning
confidence: 99%
“…Tetrahydrofuran (THF) diols are found in a wide variety of natural products [174][175][176][177]. A convenient method for the formation of THF diols is through the oxidative cyclization of 1,5-dienes to form 2,5-disubstituted THF diols.…”
Section: Stereoselective Olefin Metathesis In Synthetic Applicationsmentioning
confidence: 99%
“…(Waechter et al, 1999), larvicida contra Aedes aegypti (Dominguez-Martinez et al, 2003), atividade moduladora da resistĂȘncia bacteriana (Costa et al, 2008), bactericida e antifĂșngica (Wiart, 2007). Entretanto, destaca-se o potencial antineoplĂĄsico dessas substĂąncias, sendo promissoras no tratamento de cĂąnceres devido aos efeitos citotĂłxicos observados em linhagens tumorais e carcinomas diversos (Pettit et al, 1988;Shi et al, 1996;Shi et al, 1997;Gu et al, 1997, Kim & Park, 2002.…”
Section: Introductionunclassified